2007
DOI: 10.1111/j.1742-4658.2007.06186.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rice TUBBY‐like genes and their evolution

Abstract: The identification of TUBBY-like genes in organisms ranging from single-celled to multicellular eukaryotes has allowed the phylogenetic history of this gene family to be traced back to the early evolutionary stages of eukaryote development. Rice TUBBY-like genes were located on chromosomes 1, 2, 3, 4, 5, 7, 8, 11 and 12 without any obvious clustering. On a genomic scale, it was revealed that the rice TUBBY-like gene family probably evolved mainly through segmental duplication produced by polyploidy. The altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…In addition to a tubby domain, most plant TLPs also have an F-box domain in corresponding regions (Gagne et al 2002). The TLP family has been studied in some plant species, such as Arabidopsis (Lai et al 2004) and rice (Liu 2008). However, few studies of TLP genes have been reported in maize.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to a tubby domain, most plant TLPs also have an F-box domain in corresponding regions (Gagne et al 2002). The TLP family has been studied in some plant species, such as Arabidopsis (Lai et al 2004) and rice (Liu 2008). However, few studies of TLP genes have been reported in maize.…”
Section: Discussionmentioning
confidence: 97%
“…TUBBY-like proteins (TLPs) are present in all eukaryotes, from single-celled to multicellular organisms (Liu 2008). The typical TLP has an approximately 270-amino acid tubby domain at its C-terminus (Yang et al 2008), and most TLPs in plants also contain highly conserved F-box domains (Gagne et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Boggon et al (1999) found that the Tubby protein is a bipartite transcription regulator and that its N-terminal segment is involved in modulating transcription. In plants, Tubby proteins contain a conserved F-box domain (Liu, 2008;Yang et al, 2008). Fbox proteins regulate diverse cellular processes, including cell cycle transition, transcriptional regulation, and signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis-Piriformospora indica interaction [16][17][18] In Arabidopsis, AtTLP9 acts in ABA signaling during germination and plays a role in responses to salt and drought stress. 17,19 Consistent with this, a TLP from chickpea was recently demonstrated to confer increased tolerance to salt, drought and oxidative stress when overexpressed in tobacco.…”
Section: New Insights Into the Subcellular Localization Of Tubby-likementioning
confidence: 99%
“…14,15 TLPs have been found in many eukaryotic species. 16 Although conservation of the Tubby domain in different organisms suggests important functions, little information is available for TLPs in plants. They are present in small gene families with Tubby-like proteins (TLPs) have been associated with hormone signaling and responses to abiotic and biotic stress in plants.…”
Section: Introductionmentioning
confidence: 99%